The Relationship Between Nurses’ Knowledge Band Their Ability To Perform Triage In The Emergency Department Of M. Yunus Bengkulu Hospital - Destiana, Yeyen; Sari, Fikitri Marya; Aprianti, Delta (Jurnal Kesehatan Mitra Sekawan, 2026)
Triage is one of the essential procedures in the Emergency Department (ED) that aims to determine patient care priorities based on the level of emergency. Nurses’ knowledge is one of the key factors influencing the accuracy of triage implementation according to the Standard Operating Procedure (SOP). This study aimed to determine the relationship between nurses’ knowledge and their ability to perform triage in the Emergency Department of M. Yunus Bengkulu Hospital. This study employed a cross-sectional design with a total sampling technique involving 30 nurse respondents. Data were collected using a knowledge questionnaire and a triage skill observation sheet, and analyzed using the Chi-Square test with a significance level of α = 0.05. The univariate analysis showed that most respondents had good knowledge (73.3%), adequate knowledge (16.7%), and poor knowledge (10.0%). In terms of triage ability, the majority were in the SOP-compliant category (86.7%), while the rest were non-compliant (13.3%). The bivariate analysis revealed a χ² value of 9.047 with a p-value of 0.011, indicating a statistically significant relationship between nurses’ knowledge and their ability to perform triage in the Emergency Department of M. Yunus Bengkulu Hospital. It can be concluded that there is a significant relationship between the level of nurses’ knowledge and their ability to perform triage. The higher the level of nurses’ knowledge, the greater the likelihood that triage will be carried out in accordance with the SOP.